2019
DOI: 10.1111/ddg.13759
|View full text |Cite
|
Sign up to set email alerts
|

Deprescribing in dermatology: a systematic review of current dermatological guidelines

Abstract: ZusammenfassungAls "Deprescribing" wird der systematische Prozess der Identifikation, der Dosisreduktion und des Absetzens individuell ineffektiver und/oder potenziell schädigender Arzneimittel bezeichnet. Die hier vorgenommene Analyse befasst sich mit diesem Begriff im Rahmen der Anwendungsempfehlungen von Systemmedikationen innerhalb aktueller dermatologischer Leitlinien unter Betrachtung verschiedener Gesichtspunkte. Untersucht wurden 16 Leitlinien der Deutschen Dermatologischen Gesellschaft (DDG). Bei der … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…One of these reviews focused on frail older populations and one on palliative care patients, including cancer patients. Three other reviews focused on guidelines for discontinuation of specific medicines, e.g., cholinesterase inhibitors (94), statins (95), and dermatological therapy (96). One review described only educational materials on deprescribing one or more medicines (97), and another review determined the applicability of the N-of-1 trial method (98).…”
Section: Reviews Describing Tools For Deprescribing Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these reviews focused on frail older populations and one on palliative care patients, including cancer patients. Three other reviews focused on guidelines for discontinuation of specific medicines, e.g., cholinesterase inhibitors (94), statins (95), and dermatological therapy (96). One review described only educational materials on deprescribing one or more medicines (97), and another review determined the applicability of the N-of-1 trial method (98).…”
Section: Reviews Describing Tools For Deprescribing Approachesmentioning
confidence: 99%
“…Tools for deprescribing approaches could be applied in different stages of deprescribing, e.g., preparation, which includes assessment of the current status of the patient and his medication history, medicine evaluation, decision making, and implementation (91). The identified weaknesses of the tools in the reviews include poor descriptions of development methodology and their limited application in clinical practice (92), no or few specific recom mendations for the discontinuation of specific medicines (94)(95)(96), and in the case of educational material, a requirement of high levels of reading, thus making it inappropriate for populations with low health literacy (97). An N-of-1 or single-subject clinical trial is a randomized crossover study design in which a single patient acts as their own control (98).…”
Section: Reviews Describing Tools For Deprescribing Approachesmentioning
confidence: 99%
“…A manual search of reference lists did not yield any additional relevant publications. Ultimately, 23 records, including 15 systematic reviews 12,[14][15][16][17][18][19][34][35][36][37][38][39][40][41] and eight guidelines, [42][43][44][45][46][47][48][49] were included in this review (Figure 1). The detailed characteristics of these systematic reviews and guidelines can be found in Tables 1 and 2, respectively.…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%
“…The quality assessment of the included studies revealed that 11 systematic reviews demonstrated a low risk of bias, 12,15,[17][18][19]35,36,[38][39][40][41] while the remaining reviews exhibited a moderate 14,16 or high risk of bias. 34,37 Among the guidelines, 7 (77.8%) were considered of high quality in terms of their development, [42][43][44][45]47,49,52 while 2 (22.2%) were rated as moderate quality. 48,50 Four guidelines fully met all items of the AGREE-II assessment tool, further supporting their high quality.…”
Section: Study Selection and Quality Assessmentmentioning
confidence: 99%